On Some Class of $n$-Normed Generalized Difference Sequences Related to $\ell_p$-Space (Analysis in Theory and Applications, 2014)
In this paper, we introduce the class of $n$-normed generalized difference sequences related to $\ell_p$-space. Some properties of this sequence space like solidness, symmetricity, convergence-free etc. are studied. We obtain some inclusion relations involving this sequence space.
Keywords: Generalized difference operator; $n$-norm; $n$-Banach space; symmetricity; solidness; convergence free; completeness.